Áreas de risco para a disseminação da febre amarela em São Paulo: como a estrutura da paisagem influencia a abundância e a conectividade funcional para Haemagogus spp - Prado, Amanda Francisco (2023)
Wild yellow fever (WYF) is a high lethality infectious disease for humans and some non-human primates (NHP). It is caused by Flavivirus that have the mosquitoes Haemagogus leucocelaenus and Haemagogus janthinomys (Culicidae:Diptera) as primary vectors in the Atlantic Forest. Both species are considered acrodendrophiles and common in forest fragments, but have different tolerances to habitat degradation. Previously endemic to the Amazon region, WYF has recently spread throughout Brazil. In São Paulo state, the last WYF outbreak began in 2016 in the northwest region and, from 2017, the virus spread to the eastern part of the state, possibly through ecological corridors or stepping stones, causing a large decline in threatened PNH species and having a large impact on public health. Virus transmission risk is mainly related to vector abundance. However, despite of several efforts, little is known about vector ecology requirements, particularly on how landscape parameters affect their abundances and functional connectivity for them, which allows virus spread to other regions. Therefore, the goals of this study were (1) to analyze how and at what scale the landscape structure affects Hg. leucocelaenus and Hg. janthinomys abundance in São Paulo state, (2) based on their ecology, identify connecting elements that possibly were used by the vectors in the last outbreak and (3) indicate areas with greater risk of WYF vector dispersion. For this, we used vector abundance data collected in 24 points of native vegetation areas in São Paulo northwest and a model selection approach, with landscape metrics at different scales (from 500 m to 2.5 km) as predictor variables. Based on the best selected model, the abundance of each vector was extrapolated to the entire state and overlapped with a potential functional connectivity map developed for each species. The abundance of Hg. leucocelaenus responded to the landscape structure mainly at the 2.0 km scale and the results suggest that increases in the forest cover amount with high fragmentation levels tend to increase the abundance of this species. The abundance of Hg. janthinomys responded to the landscape structure mainly at the largest scales (2.5 km) and results suggest that this species is less abundant in fragmented and degraded landscapes, is more related to core areas of native vegetation fragments and may be more related to Cerrado areas than Hg. leucocelaenus. The areas with greatest risk for virus spread were mainly concentrated on the upper edges of Serra do Mar, in the Serra da Cantareira region, in the peripheral areas of São Paulo metropolitan region and in Vale do Paraíba, due to the greater estimated vector abundance and high functional connectivity observed. Core areas of large forest fragments showed a lower risk of virus spreading. Thus, the fragmented landscapes of São Paulo present several characteristics that result in a high risk of occurrence and WYF spread, including in areas close to large urban centers, raising the alarm of WYF reurbanization. Therefore, the maintenance and recovery of forest areas in a non-fragmented state is essential to prevent new WYF outbreaks, as well as the inclusion of multiscale analysis in the epidemiological surveillance routine and animal health services, to more accurately estimate the potential dispersion routes of the virus.